Tumor-associated macrophages and macrophage-related immune checkpoint expression in sarcomas. (1st January 2020) - Dancsok, Amanda R.; Gao, Dongxia; Lee, Anna F.; Steigen, Sonja Eriksson; Blay, Jean-Yves; Thomas, David M.; Maki, Robert G.; Nielsen, Torsten O.; Demicco, Elizabeth G.
ABSTRACT: Early trials for immune checkpoint inhibitors in sarcomas have delivered mixed results, and efforts to improve outcomes now look to combinatorial strategies with novel immunotherapeutics, including some that target macrophages. To enhance our understanding of the sarcoma immune landscape, we quantified and characterized tumor-associated macrophage infiltration and expression of the targetable macrophage-related immune checkpoint CD47/SIRPα across sarcoma types. We surveyed immunohistochemical expression of CD68, CD163, CD47, and SIRPα in tissue microarrays of 1242 sarcoma specimens (spanning 24 types). Non-translocation sarcomas, particularly undifferentiated pleomorphic sarcoma and dedifferentiated liposarcoma, had significantly higher counts of both CD68+ and CD163+ macrophages than translocation-associated sarcomas. Across nearly all sarcoma types, macrophages outnumbered tumor-infiltrating lymphocytes and CD163+ (M2-like) macrophages outnumbered CD68+ (M1-like) macrophages. These findings were supported by data from The Cancer Genome Atlas, which showed a correlation between increasing macrophage contributions to immune infiltration and several measures of DNA damage. CD47 expression was bimodal, with most cases showing either 0% or >90% tumor cell staining, and the highest CD47 scores were observed in chordoma, angiosarcoma, and pleomorphic liposarcoma. SIRPα scores correlated well with CD47 expression. Given the predominance of macrophage infiltrates over tumor-infiltrating lymphocytes, the bias toward M2-like (immunosuppressive) macrophage polarization, and the generally high scores for CD47 and SIRPα, macrophage-focused immunomodulatory agents, such as CD47 or IDO-1 inhibitors, may be particularly worthwhile to pursue in sarcoma patients, alone or in combination with lymphocyte-focused agents.